Functional Popliteal Artery Entrapment Syndrome: An Approach to Diagnosis and Management - Lovelock, Thomas; Claydon, Matthew; Dean, Anastasia (International Journal of Sports Medicine, 2021)
Popliteal Artery Entrapment Syndrome (PAES) is an uncommon syndrome that predominantly affects young athletes. Functional PAES is a subtype of PAES without anatomic entrapment of the popliteal artery. Patients with functional PAES tend to be younger and more active than typical PAES patients. A number of differential diagnoses exist, the most common of which is chronic exertional compartment syndrome. There is no consensus regarding choice of investigation for these patients. However, exercise ankle-brachial indices and magnetic resonance imaging are less invasive alternatives to digital subtraction angiography. Patients with typical symptoms that are severe and repetitive should be considered for intervention. Surgical intervention consists of release of the popliteal artery, either via a posterior or medial approach. The Turnipseed procedure involves a medial approach with a concomitant release of the medial gastrocnemius and soleal fascia, the medial tibial attachments of the soleus and excision of the proximal third of the plantaris muscle. Injection of botulinum A toxin under electromyographic guidance has recently shown promise as a diagnostic and/or therapeutic intervention in small case series. This review provides relevant information for the clinician investigating and managing patients with functional PAES.
Keywords: functional PAES; chronic exertional compartment syndrome; exertional leg pain